Novel Streptomycete antimicrobial compounds: activity against pathogens from domestic rainwater harvesting systems - Durrell, Kim Angeline (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.